UPAYA MENINGKATKAN MINAT SISWA TERHADAP KEGIATAN EKSTRAKURIKULER DRUMBAND DI SMK NEGERI 2 PADANG - Fitriani, Nursyah; Yensharti, Yensharti (SENDRATASIK UNP, 2019)
Abstract This study aims to increase students' interest toward drum band extracurricular activity in SMKN 2 Padang. This study was qualitative with using descriptive data processing. Data were collected based on the results of library research, observations and interviews. The instrument used in this study was the researcher and the supporting instruments used notebooks, stationery, photo cameras / cellphones, and song scores.Based on the result of the study, it is found that the efforts to increase students’ interest toward drum band extracurricular activity in SMK N 2 Padangwere carried out by using some ways, first, the trainer gives motivation tostudents, then practices by guided practice, and appoints a friend as a tutor to teach friends who are not good at song material. Then, supporting from the school by encouraging and completing facilities and infrastructures such as buying new musical instruments and finally, the support that are  given by parents to students. By doing some efforts that are made by the trainer and the school, the students’ interest increase to take part in this extracurricular activity. It can be seen from the number of students attendance at each meeting and how fast students in mastering the song material that is given by the trainer. Keywords: effort, student interest, extracurricular drum band activities